STUDENTS GROUPING CAN INCREASE STUDENTS’ PERFORMANCE - Kubaščíková, Zuzana; Juhászová, Zuzana; Tumpach, Miloš (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
Educational facilities are under increasing pressure to improve the quality of education and adhere the curriculum that reflect the needs of practice. In order to be able to meet this goals, schools and universities apply different methods of organizing learning process. This paper presents an evaluation of the system of grouping students into study groups. The paper is devoted to the analysis of comparison of study results compared with their results from entrance exams two measurements carried out on students of three-year bachelor study with economic focus. The purpose of this study is to choose the system of grouping students to increase performance of students.